Verificação e habilitação de créditos na lei de falências e recuperação de empresas - Silva, Alice Rodrigues (2008)
This work consists of the study of the verification of credits in the bankruptcy process and Judicial Recovery, considered the most important phase of the bankruptcy proceeding by the time when the credits will be admitted and classified for payment, which makes the study of fundamental relevance. The purpose of this research, in a broad sense, is to to analyze the normative provisions regarding the qualifications of the credits set forth in Law no. 11.101 / 2005, in a comparative study to the provisions of the repealed Decree No. 7.661 / 1945, verifying how the qualification phase takes place and which points are the most prominent. In sense strictly speaking, it is intended to clarify this phase of the bankruptcy procedure, demonstrating how verification of the credits is effective in a satisfactory manner. Therefore, we will study the contingency, such as the impugnation, and the homologation of the general framework of creditors, with the classification established by law for the effective payments.